Preparatory Year Students' Perception of Pharmacy Profession as a Career Choice: A Cross-Sectional Study - Fowad Khurshid; Fahad Alharbi; Abdulrahman Almohydib; Shatha Ibn Malik; Hussain A. Al-Omar; Mohammed S. Alsultan; Abdlatif Alghaiheb (Universidade de São Paulo, 2023)
Abstract The study attempted to assess preparatory year students' perception towards pharmacists and the pharmacy profession. This cross-sectional survey was conducted between December 2019 and March 2020. The students were invited to complete an anonymous questionnaire via Google Forms®. In total, 244 students, of which 53.7% were female with the mean age of 19.2 ± 0.65, from 12 universities participated in this study. As per our findings, the majority of the respondents (91.8%) regard pharmacy as a well-respected profession, 82.4% thought pharmacists are important decision-makers, 68.4% disagreed that most pharmacists were unkind, and 60.7% did not agree that pharmacy was a low-status occupation. Meanwhile, 95.5% agreed that pharmacists must have a university degree, 88.6% agreed pharmacists must take responsibility for patients, and 82.8% believed pharmacists had to work too hard. Moreover, 62.3% did not think pharmacy was a low-skill occupation, 54.9% did not agree pharmacists must do unpleasant things, and 45.1% disagreed pharmacists only did what physicians requested of them. Lastly, 48.8% had low confidence in choosing pharmacy as a career. The students' overall perception toward pharmacists and the pharmacy profession was favorable. However, only one-fourth of the students displayed a tendency to choose pharmacy as a future career.